Teachers’ Satisfaction and Perceived Stress in Science Teaching: A Mixed-Methods Study - Carmen, Jesson; Balanga, Gerald Jayson B. (Future Science / FSH-PH Publications, 2024)
The COVID-19 pandemic drastically impacted the world of education, influencing teachers' levels of stress and satisfaction. While numerous studies address teacher stress and job satisfaction, there is a paucity of evidence in the context of public senior high school science teachers in science instruction during a global health crisis. This explanatory sequential mixed-methods study examined the relationship between levels of science teaching satisfaction and perceived stress, as well as the factors contributing to teachers' satisfaction and stress. The researchers utilized standardized instruments and in-depth interviews with the research participants. Results showed that science teachers had average job satisfaction and moderately perceived stress in science teaching. The levels of perceived stress and job satisfaction between education and non-teacher education graduates are comparatively similar. Meanwhile, the study found a non-significant negative relationship between science teaching satisfaction and perceived stress. Furthermore, factors such as workplace culture, student learning, good compensation with opportunities for promotion, and professional development programs were found to impact teachers’ satisfaction in science teaching. Factors contributing to teachers’ perceived stress included the COVID-19 pandemic, availability of teaching and learning resources, limited contact hours, demands for submission of reports and other paperwork, student behavior and attitude towards studies, and teacher-specific factors. Finally, suggestions from the science teachers to reduce stress entailed maintaining work-life balance, exercising proper time management, reduced workloads to allow for a focus on teaching, and promoting collaboration among science teachers.